Replicase-based plasmid DNA shows anti-tumor activity - Weiss Richard; Chung Woon-Gye; Yu Zhen; Rodriguez B Leticia; Cui Zhengrong (BMC Cancer, 2011)
Abstract Background Double stranded RNA (dsRNA) has multiple anti-tumor mechanisms. Over the past several decades, there have been numerous attempts to utilize synthetic dsRNA to control tumor growth in animal models and clinical trials. Recently, it became clear that intracellular dsRNA is more effective than extracellular dsRNA on promoting apoptosis and orchestrating adaptive immune responses. To overcome the difficulty in delivering a large dose of synthetic dsRNA into tumors, we propose to deliver a RNA replicase-based plasmid DNA, hypothesizing that the dsRNA generated by the replicase-based plasmid in tumor cells will inhibit tumor growth. Methods The anti-tumor activity of a plasmid (pSIN-β) that encodes the sindbis RNA replicase genes (nsp1-4) was evaluated in mice with model tumors (TC-1 lung cancer cells or B16 melanoma cells) and compared to a traditional pCMV-β plasmid. Results In cell culture, transfection of tumor cells with pSIN-β generated dsRNA. In mice with model tumors, pSIN-β more effectively delayed tumor growth than pCMV-β, and in some cases, eradicated the tumors. Conclusion RNA replicase-based plasmid may be exploited to generate intracellular dsRNA to control tumor growth.